Testing the inter-hemispheric competition account of visual extinction with combined TMS/fMRI. (July 2015) - Petitet, Pierre; Noonan, MaryAnn P.; Bridge, Holly; O'Reilly, Jill X.; O'Shea, Jacinta
Abstract: Theoretical models of visual neglect and extinction entail claims about the normal functioning of attention and parietal cortex in the healthy brain: (1) 'pseudoneglect', a commonly observed attentional bias towards left space, reflects the greater dominance of parietal cortex activity of the right versus left hemisphere; (2) the capacity to distribute attention bilaterally depends causally on the relative balance of parietal activity between the hemispheres; (3) disruption of the dominant right parietal cortex shifts this inter-hemispheric balance leftward, causing a rightward shift in attentional bias. We tested these claims using low-frequency offline transcranial magnetic stimulation (TMS) to transiently inhibit activity in the right angular gyrus/intra-parietal sulcus, followed by a visual detection task to assess changes in attentional bias, and functional magnetic resonance imaging (fMRI) to test for the predicted leftward shift in brain activity. The task required participants to covertly monitor both hemifields to detect and report the location of upcoming transient visual targets that appeared on the left, right or bilaterally. In the behavioural experiment, participants exhibited a leftward attentional bias ('pseudoneglect') at baseline, which was abolished by TMS. In the fMRI experiment, participants activated an expected network of visual, parietal and frontal cortex bilaterally during the period of covert bilateral attention. TMS shifted the relative hemispheric balance of parietal activity from right to left. The consistent direction of TMS-induced behavioural and functional change indicates a causal role for parietal inter-hemispheric balance in distributing visual attention across space. Highlights: Right PPC TMS shifted hemispheric balance of parietal fMRI activity leftward. Right PPC TMS shifted bilateral attention rightward, simulating 'extinction'. Consistent brain/behaviour change implicates hemispheric balance in extinction.